2006
DOI: 10.1002/rcm.2764
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography/tandem mass spectrometry assay for the quantification of troxerutin in human plasma

Abstract: A simple, rapid, sensitive and specific liquid chromatography/tandem mass spectrometry method was developed and validated to quantify troxerutin in human plasma. The analyte and rutin, used as the internal standard, were analyzed on a Phenomenex Synergi Fusion RP column interfaced with a triple-quadrupole tandem mass spectrometer using positive electrospray ionization. Acetonitrile/water (20:80 v/v) was used as the isocratic mobile phase, with 0.1% formic acid in water. A simple sample preparation method of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 9 publications
2
21
0
4
Order By: Relevance
“…This is because protein precipitation with perchloric acid does not remove water soluble impurities which would enhance the matrix effects. What is clear is that the assay reported here gives similar sensitivity to that as in [10] (LLOQ 0.01 ng mL -1 using 150 lL plasma vs. 0.025 ng mL -1 using 100 lL plasma) in a shorter cycle time (3.3 vs. 4.5 min) with improved accuracy and precision.…”
Section: Methods Validationsupporting
confidence: 52%
See 3 more Smart Citations
“…This is because protein precipitation with perchloric acid does not remove water soluble impurities which would enhance the matrix effects. What is clear is that the assay reported here gives similar sensitivity to that as in [10] (LLOQ 0.01 ng mL -1 using 150 lL plasma vs. 0.025 ng mL -1 using 100 lL plasma) in a shorter cycle time (3.3 vs. 4.5 min) with improved accuracy and precision.…”
Section: Methods Validationsupporting
confidence: 52%
“…In the LC-MS-MS assay of troxerutin in human plasma reported by Liu et al [10], protein precipitation with perchloric acid produced variable matrix effects (93. and \9.03%, respectively. This is because protein precipitation with perchloric acid does not remove water soluble impurities which would enhance the matrix effects.…”
Section: Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature survey shows that, the relatively new Synergi Fusion-RP column employed in the present study has been in use since 2006 but has been utilized in only a few scientific studies. Two of those investigations 29,30 indicated that the Synergi column offered chromatographic benefits, and one 31 suggested that it has drawbacks compared to other columns, and the remaining four studies merely mentioned that the Synergi column had been used, without any further comments.…”
Section: Chromatographic Retardationmentioning
confidence: 99%